Analysis of English Teaching Mode in Big Data Environment Based on Hadoop Cloud Platform. Issue 2 (August 2021) - Zhang, Linfei
Abstract: With the continuous deepening of the application of big data technology, the education field is also paying attention to the impact of big data. "Internet +" education has become a hot topic in the current education field. This article relies on the big data Hadoop cloud platform technology through integration lines Online and offline resources and a variety of teaching techniques and methods are used to analyze the business English teaching model, and use the mixed teaching model to promote the development from extensive to standardization, aiming to enhance the richness, interaction and effectiveness of business English teaching.